The flight portfolio - Orringer, Julie (Alfred A. Knopf, 2019)
"The long-awaited new work from the best-selling author of The Invisible Bridge takes us back to occupied Europe in this gripping historical novel based on the true story of Varian Fry's extraordinary attempt to save the work, and the lives, of Jewish artists fleeing the Holocaust. In 1940, Varian Fry--a Harvard educated American journalist--traveled to Marseille carrying three thousand dollars and a list of imperiled artists and writers he hoped to rescue within a few weeks. Instead, he ended up staying in France for thirteen months, working under the veil of a legitimate relief organization to procure false documents, amass emergency funds, and set up an underground railroad that led over the Pyrenees, into Spain, and finally to Lisbon, where the refugees embarked for safer ports. Among his many clients were Hannah Arendt, Franz Werfel, Andre Breton, Max Ernst, Marcel Duchamp, and Marc Chagall. The Flight Portfolio opens at the Chagall's ancient stone house in Gordes, France, as the novel's hero desperately tries to persuade them of the barbarism and tragedy descending on Europe. Masterfully crafted, exquisitely written, impossible to put down, this is historical fiction of the very first order, and resounding confirmation of Orringer's gifts as a novelist"--